Effect of Starvation on the Biochemical Composition of Freshwater Fish Channa punctatus - Chavan Pallavi, Sunnap Namrata, Nanware Sanjay* and (Recent Research in Science and Technology, 2011)
The present study was carried out to study the changes in Biochemical constituents in different tissues of freshwater fish, Channa punctatus studied during starvation. The experiment involved 30 individuals of Channa punctatus (species) caught from Godavari river water. At the end of the experimental period, the tissues for biochemical analysis are collected separately from control and starved fishes. Starving resulted in body weight reduction and decrease in biochemical content in fish.